2012
DOI: 10.3767/000651912x652012
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of the Malesian species of Lasianthus (Rubiaceae)

Abstract: Based on herbarium collections, the Malesian species of the genus Lasianthus are revised. A total of 131 species including 5 subspecies and 6 varieties are recognized from the Malesian region, of which 41 species, 3 subspecies and 3 varieties are described as new, and 3 new combinations are made for varieties. 22 species names and 15 variety names are reduced to synonyms. Ten species names and 2 varieties are treated as dubious mainly because their types cannot be traced. Additionally, 11 species are further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 14 publications
0
46
0
3
Order By: Relevance
“…Firstly, we reviewed all authoritative botanical data including Flora [12], related journals and botanical texts assembling details on plant distribution, morphological characteristics, medicinal uses and modes of preparation. We then crossreferenced these data via online databases and compared them with herbaria records in Thailand, Aarhus University Herbarium, Denmark and The Kew Herbarium, The United Kingdom.…”
Section: Ethnomedicinal Plants Reviewmentioning
confidence: 99%
“…Firstly, we reviewed all authoritative botanical data including Flora [12], related journals and botanical texts assembling details on plant distribution, morphological characteristics, medicinal uses and modes of preparation. We then crossreferenced these data via online databases and compared them with herbaria records in Thailand, Aarhus University Herbarium, Denmark and The Kew Herbarium, The United Kingdom.…”
Section: Ethnomedicinal Plants Reviewmentioning
confidence: 99%
“…The genus Lasianthus (Rubiaceae) includes about 180 species of which 160 occur in primary forests in tropical Asia (Robbrecht 1988, Zhu et al 2012. In Southeast Asia alone, there are more than 130 species which have been treated separately for different parts of the region.…”
mentioning
confidence: 99%
“…Lasianthus Jack is one of the largest genera within Rubiaceae with about 180-228 species listed throughout the tropical regions (Davis et al, 2009;Zhu et al, 2012). However, the centre of its diversity is concentrated in the Malesian region with 131 species enumerated (Zhu et al, 2012), with new species still being discovered as more botanical explorations were conducted in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In January 2017, we re-studied the Rubiaceae collections gathered from Wawonii with a specific interest focusing on Lasianthus. After having examined the materials thoroughly using the treatment by Zhu et al (2012), we concluded that Lasianthus sp. 1 (represented by specimen number: Siti Sunarti SS 206) Shrub, generally covered with long hirsute hairs throughout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation